The fungi - Watkinson, Sarah C.; Boddy, Lynne; Money, Nicholas P. (Academic Press is an imprint of Elsevier, 2015)
"The Fungi, Third Edition offers a comprehensive and thoroughly integrated treatment of the biology of the fungi. This modern synthesis highlights the scientific foundations that continue to inform mycologists today, as well as recent breakthroughs and the formidable challenges in current research. The Fungi combines a wide scope with the depth of inquiry and clarity offered by three leading fungal biologists. The book describes the evolution and astonishing diversity of the fungi, their genetics and complex life cycles, and intriguing mechanisms of spore release. The distinctive cell biology of the fungi is linked to their development as well as their metabolism and physiology. Fungi interact with plants and animals and are major players in global nutrient cycles. Plants and animals are supported by mutualistic relationships with fungi, damaged by pathogenic species, and their dead tissues are recycled by saprotrophic fungi. This book is written for undergraduates and graduate students, and is also useful for professional biologists interested in specific topics in fungal biology."--Page 4 of cover.